Such Great Heights: The Complete Cultural History of the Indie Rock Explosion : The Complete Cultural History of the Indie Rock Explosion - DeVille, Chris (New York : St. Martin's Press, 2025)
"The definitive history of 21st century indie rock-from Iron & Wine and Death Cab for Cutie to Phoebe Bridgers and St. Vincent-and how the genre shifted the musical landscape and shaped a generation. Maybe you caught a few exhilarating seconds of "Teen Age Riot" on a nearby college radio station while scanning the FM dial in your parents' car. Maybe your friend invited you to a shabby local rock club and you ended up having a religious experience with Neutral Milk Hotel. Perhaps you were scandalized and tantalized upon sneaking Liz Phair's Exile in Guyville from an older sibling's CD collection, or you vowed to download every Radiohead song you could find on Limewire because they were the favorite band of the guy you had a major crush on. However you found your way into indie rock, once you were a listener, it felt like being part of a secret club of people who had discovered something special, something secret, something superior. In Such Great Heights, music journalist Chris DeVille brilliantly captures this cultural moment, from the early aughts and the height of indie rock, until the 2010s as streaming rocks the industry and changes music forever. DeVille covers the gamut of bands-like Arcade Fire, TV on the Radio, LCD Soundsystem, Haim, Pavement, and Imogen Heap-and in the vein of Chuck Klosterman's The Nineties, touches on staggering pop culture moments like sharing music recommendations via AOL Instant Messenger and the life-changing OC soundtrack. Nerdy, fun, and a time machine for millennials, Such Great Heights is about how subculture becomes pop culture, how capitalism consumes what's "cool," about who gets to define what's hip and how, and how an "underground" genre shaped our lives"--.
new book 2025 fall.
Includes bibliographical references and index.
Keywords: Indie pop music -- United States -- History and criticism; Popular culture -- United States -- History -- 20th century; Popular culture -- United States -- History -- 21st century; Alternative music; Rap music